Characteristics and Kinetics Study of Glycerolabietate from Glycerol and Abietic Acid from Rosin - Danang Tri Hartanto; Rochmadi Rochmadi; Meiga Putri Wahyu; Diastari Kusumawati (Departemen Teknik Kimia Fakultas Teknik Universitas Gadjah Mada, 2021)
Rosin is a natural resin from the coniferous tree sap, which separated from its oil content (terpenes). Rosin is brittle. Therefore modifications are needed to improve its mechanical properties. The main content of rosin is abietic acid which has a carboxylic group, so it can form an ester group when reacted with polyhydric alcohol (polyalcohol) such as glycerol. The research aimed to study the kinetics of the esterification reaction between the hydroxyl group in glycerol and the carboxylic group in abietic acid from rosin at various reaction temperatures and reactant compositions. This reaction is carried out in a three-neck flask at atmospheric pressure without a catalyst. The reaction temperatures used were 180˚C, 200˚C, and 220˚C, and the ratio of rosin and glycerol was 1:1, 1:3, and 1:5. The reaction kinetics calculations were analyzed with acid number data over the reaction time using three different models. The calculations showed that this reaction involves positioning a hydroxyl group on glycerol, which the primary and secondary hydroxyl groups contribute to forming a rosin ester (glycerolabietate). The rate of reaction constants of primary hydroxyl of glycerol and abietic acid were in the range 6.25x10-4 - 3.90x10-3 g/(mgeq.min), while reaction rate constants of secondary hydroxyl and abietic acid were in the range 1.06x10-5 - 1.15x10-4 g/(mgeq.min). FTIR analysis showed a change in the hydroxyl, carboxylate, and ester groups which were assigned by a shift of wavenumber and a difference of intensity at 3200-3570 cm-1, 1697.36 cm-1, and 1273.02 cm-1.